Metabolism of N-Acylated-Dopamine - Zajac, Dominika; Spolnik, Grzegorz; Roszkowski, Piotr; Danikiewicz, Witold; Czarnocki, Zbigniew; Pokorski, Mieczyslaw (PLOS ONE, 2014)
N-oleoyl-dopamine (OLDA) is a novel lipid derivative of dopamine. Its biological action includes the interaction with dopamine and the transient receptor potential vanilloid (TRPV1) receptors. It seems to be synthesized in a dopamine-like manner, but there has been no information on its degradation. The aim of the study was, therefore, to determine whether OLDA metabolism proceeds the way dopamine proper does. We addressed the issue by examining the occurrence of O-methylation of exogenously supplemented OLDA via catechol-O-methyltransferase (COMT) under in vitro, ex vivo, and in vivo conditions using rat brain tissue. The results show that OLDA was methylated by COMT in all conditions studied, yielding the O-methylated derivative. The methylation was reversed by tolcapone, a potent COMT inhibitor, in a dose-dependent manner. We conclude that OLDA enters the metabolic pathway of dopamine. Methylation of OLDA may enhance its bioactive properties, such as the ability to interact with TRPV1 receptors.